Gracilaria manilaensis as an alternative food source - Abdullah, Najatul Su Ad; Mohammad Noor, Normawaty; Zainal Abidin, Zaima Azira; Mohamad, Mohd Azrul Naim (2018)
Red seaweeds, Rhodophyta, are very beneficial as a good source of nutrients, collagen, and bioactive metabolites. Thus, seaweeds are consumed or harvested for various industries including processed food and nutraceuticals. The good contents of the seaweeds are due to the interactions between the seaweeds and its holobiont environment which hosts microorganisms such as fungi and bacteria. Gracilaria manilaensis is often found in coastal villages of peninsular Malaysia and eaten as a local delicacy, “Kerabu Sare”. However, little is known on its nutritional content, therapeutic properties or associated bacteria though studies of bacteria associated to other Rhodophyta species have been conducted worldwide. Studying associated bacteria with halogenase functional genes will provide understanding on how symbiotic bacteria benefits the edible red seaweed, G. manilaensis. Total of 4 seaweed samples have been collected from Bidong Island (1), Kedah seaweed farm (1) and Pulau Pinang (2). DNA from seaweed samples were extracted by CTAB method and were sent for amplicon sequencing. Bacteria were cultured on 8 selectively enriched media and 97 cultivated bacteria isolates from 1022 total colony were identified through PCR, partial sequencing, and sequence BLAST. Bacteria sequence data was then clustered into 38 OTUs and the isolates were identified to belong to 4 phyla namely Proteobacteria (alpha and gamma), Firmicutes, Actinobacteria, and Bacteriodetes. Additionally, 22 isolates were positive for halogenase bromoperoxidase functional gene screening. Knowledge of these symbiotic bacteria isolated from red seaweed, G. manilaensis, will help us understand the ecosystem that the seaweeds thrive in. Farming of the seaweed will help towards the economy of rural areas. Furthermore, well-maintained coastal areas with booming sea life and vegetation like corals, fishes, and seaweeds can also boost ecoedutourism.